Building Innovative Learning With A Digital Curriculum: A Steps Towards Disruptive Education - Aulia, Gita Nur; Saka, Agum; Abdurrahmansyah, Abdurrahmansyah (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Amidst the digital transformation happening in the current era, the world of education must adapt by using more creative and relevant teaching methods. It is considered that the conventional curriculum does not meet all the needs of the 21st-century challenges, which emphasize creativity, digital literacy, collaboration, and problem-solving. Therefore, a digital curriculum-based education system must be created immediately. This study aims to determine how a digital curriculum can make the learning system more flexible, interactive, and focused on improving all students' abilities. This method is expected to enable the education system to create a learning environment that is more in line with the dynamics of the times. This method is also expected to support the formation of a generation ready to compete in the global market.